A novel chaotic flower pollination algorithm for global maximum power point tracking for photovoltaic system under partial shading conditions - Yousri D.; Babu T.S.; Allam D.; Ramachandaramurthy V.K.; Etiba M.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Global optimization; Photovoltaic cells; Algorithm parameters; Environmental conditions; Environmental phenomena; Global maximum power point tracking; Maximum power point tracking techniques; Optimization algorithms; Photovoltaic systems; Standard versions; Maximum power point trackers